2018
DOI: 10.1038/s41598-018-22471-x
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Nomogram for Postoperative Bone Remodeling in Patients with ADDWoR

Abstract: This study aimed to establish an effective prognostic nomogram for predicting the probability of postoperative bone remodeling of patients with anterior disc displacement without reduction (ADDWoR). The nomogram was based on a retrospective study on patients underwent surgical approaches for ADDWoR at Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University from January, 2007 to January, 2017. A multivariate logistic regression analysis was used to develop variables suitable for probability estimation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Some scholars 21 , 22 have studied the bone remodeling after TMJ arthroscopic disc reposition. Liu XH et al 22 conducted a retrospective study on the formation of new bone in patients after arthroscopy through the study method of prognosis nomogram. The results showed that the rate of new bone formation after arthroscopy was about 50% considering the sex, age, Wilkes stage, bad oral habits (such as bruxism).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars 21 , 22 have studied the bone remodeling after TMJ arthroscopic disc reposition. Liu XH et al 22 conducted a retrospective study on the formation of new bone in patients after arthroscopy through the study method of prognosis nomogram. The results showed that the rate of new bone formation after arthroscopy was about 50% considering the sex, age, Wilkes stage, bad oral habits (such as bruxism).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 31 implemented a prognostic nomogram to predict the prognostic variables most associated with higher chances of successful disc repositioning, re ected by postoperative new bone formation and condylar remodeling as an important index of treatment outcome which can reverse the effects caused by ADD. They concluded that age of onset, nocturnal bruxism, disc morphology, bone marrow density, Wilkes stages, and postoperative splint therapy were signi cantly associated with bone remodeling after arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Condylar resorption was based on 2 TMJ-MRI scans with a 6-mo interval. It presented as a rough and discontinuous cortical bone outline in the sagittal view with decreased condylar height as compared with baseline (Shen et al 2014;Liu et al 2018). At 6 mo after surgery, patients again underwent TMJ-MRI; according to which, new bone formation was defined as the condyle head presenting with a double cortical phenomenon and increased condylar height as compared with baseline (Liu et al 2018;Dong et al 2021) Protein Extraction and Trypsin Digestion SF was lysed by urea (8 M), loaded with protein supernatants into 10-kD filtration devices (Microcon; Millipore), and filtered.…”
Section: Tmj-mri Examinationmentioning
confidence: 99%
“…It presented as a rough and discontinuous cortical bone outline in the sagittal view with decreased condylar height as compared with baseline (Shen et al 2014;Liu et al 2018). At 6 mo after surgery, patients again underwent TMJ-MRI; according to which, new bone formation was defined as the condyle head presenting with a double cortical phenomenon and increased condylar height as compared with baseline (Liu et al 2018;Dong et al 2021) Protein Extraction and Trypsin Digestion SF was lysed by urea (8 M), loaded with protein supernatants into 10-kD filtration devices (Microcon; Millipore), and filtered. Then, the samples were digested with trypsin.…”
Section: Tmj-mri Examinationmentioning
confidence: 99%
See 1 more Smart Citation